2019
DOI: 10.3389/fpsyg.2019.01985
|View full text |Cite
|
Sign up to set email alerts
|

Priming Effects of Focus in Mandarin Chinese

Abstract: Psycholinguistic research has long established that focus-marked words have a processing advantage over other words in an utterance, e.g., they are recognized more quickly and remembered better. More recently, studies have shown that listeners infer contextual alternatives to a focused word in a spoken utterance, when marked with a contrastive accent, even when the alternatives are not explicitly mentioned in the discourse. This has been shown by strengthened priming of contextual alternatives to the word, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 63 publications
5
33
0
Order By: Relevance
“…The question is how this typological distinction relates to the prosodic findings of the speech production study, which has shown that all languages have some prosodic reflexes of information structure. Significant prosodic effects of focus were found in all four languages in line with earlier findings; see Vander Klok et al (2018) on reflexes of different types of focus in French, Greif (2012) and Ouyang and Kaiser (2015) for the impact of contrastive focus in Chinese as well as Yan and Calhoun (2019) for effects of prosodic prominence in Chinese on interpretation (invoking alternatives). Moreover, our study shows that these prosodic effects equally appear in the constructions at issue (canonical and cleft constructions).…”
Section: General Discussion and Conclusionsupporting
confidence: 89%
“…The question is how this typological distinction relates to the prosodic findings of the speech production study, which has shown that all languages have some prosodic reflexes of information structure. Significant prosodic effects of focus were found in all four languages in line with earlier findings; see Vander Klok et al (2018) on reflexes of different types of focus in French, Greif (2012) and Ouyang and Kaiser (2015) for the impact of contrastive focus in Chinese as well as Yan and Calhoun (2019) for effects of prosodic prominence in Chinese on interpretation (invoking alternatives). Moreover, our study shows that these prosodic effects equally appear in the constructions at issue (canonical and cleft constructions).…”
Section: General Discussion and Conclusionsupporting
confidence: 89%
“…In this experiment, we adopted Birch and Clifton's (1995) RT paradigm, which was also used in Chen (2010). Similar design has been widely used in other studies on focus comprehension (e.g., Clifton Jr. & Frazier, 2016;Ito, 2002;Yan & Calhoun, 2019). On each trial, participants first listened to a short story and were presented with a questionanswer dialogue about the short story on each trial.…”
Section: Research Questions and Hypothesesmentioning
confidence: 99%
“…These studies have investigated the influence of intonation focus or focus-sensitive particles in English, German, and Dutch. As of yet, studies investigating the processing of focus alternatives in other languages are scarce (but see Yan & Calhoun, 2019, for data from Mandarin Chinese).…”
Section: Introductionmentioning
confidence: 99%